Growth and Characterization of Semiorganic Non-linear Optical Material: (((4-aminophenyl)sulphonyl)oxy)zinc(II)chloride Crystal. Issue 1 (11th December 2019) - Vinoth, E.; Vetrivel, S.; Gopinath, S.; Suresh, J.
Abstract : Growth and characterization of nonlinear optical (NLO) crystal of (((4-aminophenyl)sulphonyl)oxy)zinc(II)chloride (4-ASZC), based on zinc chloride with sulphanilic acid by the slow evaporation method has been studied and reported in this paper. The single crystal X-ray diffraction study confirmed the monoclinic system with centrometric space group P21 . The sharp Bragg's peak in powder X-ray diffraction analysis identifies the crystalline nature. Optical properties, such as low cut-off wavelength (251 nm), optical band gap ( E g  = 4.40 eV), reflectance ( R ), extinction coefficient ( K ) and refractive index ( n ), are calculated from the UV-vis-NIR spectrum. The presence of functional groups are confirmed by the FT-IR spectroscopy. The placement of protons and carbons was determined by the NMR technique. The photoluminescence study shows the green light emission. The grown crystal is thermally stable up to184°C. The NLO efficiency is 0.5 times greater than that of standard KDP. The mechanical properties were analysed. The dielectric constant (ϵ), dielectric loss (ϵ′), imaginary dielectric constant (ϵ ″ ), AC conductivity ( σ a c ) and Cole–Cole graphs were plotted. The surface morphology and the particle size of the crystal were determined by the FESEM technique.